2018
DOI: 10.1155/2018/4653109
|View full text |Cite
|
Sign up to set email alerts
|

Screening Circulating Tumor Cells as a Noninvasive Cancer Test in 3388 Individuals from High-Risk Groups (ICELLATE2)

Abstract: Cancer is known to spread up to 12 years before clinical symptoms occur, but few screening tests exist. Early detection would give the opportunity for early treatment, potentially improving prognosis. To this end, 3388 subjectively healthy individuals of age 45 to 80 who had been exposed to cancer risk factors were screened for the occurrence of circulating tumor cells in their blood. Presence of circulating tumor cells is a suspicious finding indicative of spreading cancer, since cancer metastasizes by way of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…CTC can be used to monitor treatment response and to predict prognosis (11)(12)(13). CTC has been proposed as a screening tool for lung cancer in high-risk groups of people (17). Based on the reviews of CTC in BC published in 2013 and 2016, maximum CTC detection rates in early stage and metastatic BC are 55% and 54%, respectively (11,18).…”
Section: Discussionmentioning
confidence: 99%
“…CTC can be used to monitor treatment response and to predict prognosis (11)(12)(13). CTC has been proposed as a screening tool for lung cancer in high-risk groups of people (17). Based on the reviews of CTC in BC published in 2013 and 2016, maximum CTC detection rates in early stage and metastatic BC are 55% and 54%, respectively (11,18).…”
Section: Discussionmentioning
confidence: 99%
“…CTCs are tumor cells that can be used to screen and classify high-risk tumors (40). Studies have shown that CTC counts are variable in different subtypes and stages of breast cancer, and that CTCs are more frequently observed in advanced stages compared with in early stages (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Castro et al have evaluated blood samples of 3388 individuals aged 45-80 years with no cancer history. They found circulating non-haematological cells in the blood of 107 (3.2%) individuals (67). In lung cancer, there were attempts to combine CTC assessment with established screening methods.…”
Section: Utilization Of Ctc In Monitoring Disease Developmentmentioning
confidence: 99%